2015
DOI: 10.1111/ijs.12619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helicopter transport on neurological outcomes in a mouse model of embolic stroke with reperfusion: AIR-MICE pilot study

Abstract: This study shows that helicopter emergency medical services do not have an inherent adverse effect on outcome in a mouse model of ischemic stroke with reperfusion. These results endorse the safety of the practice of using helicopter emergency medical services in stroke patients. The observed potential synergistic effect of helicopter-induced factors, such as vibration and changes in altitude, with reperfusion merits further exploration in animal experimental models and in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Transport by helicopter has been reported to be safe in animal experimental models as well as in human patients with stroke. 1820) Currently, we use a 24-h helicopter transportation system consisting of three types of helicopter: HEMS, an MSDF helicopter, and an FDP helicopter. Helicopter transport from the islands to our hospital using an MSDF helicopter was started in the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Transport by helicopter has been reported to be safe in animal experimental models as well as in human patients with stroke. 1820) Currently, we use a 24-h helicopter transportation system consisting of three types of helicopter: HEMS, an MSDF helicopter, and an FDP helicopter. Helicopter transport from the islands to our hospital using an MSDF helicopter was started in the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low-frequency vibration may lead to an increase in blood-brain barrier permeability or the hypobaric environment may worsen the ischemic penumbra. 16,17 However, some of the environmental factors could be beneficial for the thrombus. 17 The accelerations and low frequency vibrations associated with HEMs transfer may be synergistic with rtPA and enhance the thrombolysis effectiveness of rtPA.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 However, some of the environmental factors could be beneficial for the thrombus. 17 The accelerations and low frequency vibrations associated with HEMs transfer may be synergistic with rtPA and enhance the thrombolysis effectiveness of rtPA. 18,19 The vibration effects in conjunction with thrombolysis have been shown to increase the rate of recanalization compared to thrombolysis alone.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized pilot study on a murine embolic model suggested that helicopter transport did not negatively influence outcomes, and in fact the trend was towards smaller infarctions and hemorrhage. 42 Clearly, the potential influence of HEMS physical factors on stroke outcomes needs to be studied further. It is crucial to understand the net effect and interaction of those physical factors in order to optimize the delivery of thrombolytic agents, best medical care, and eventual neuroprotective agents, for drip and ship stroke patients.…”
Section: Physical Factor Potential Effectmentioning
confidence: 99%
“…It is crucial to understand the net effect and interaction of those physical factors in order to optimize the delivery of thrombolytic agents, best medical care, and eventual neuroprotective agents, for drip and ship stroke patients. 42 Current ancillary care in patients transported through HEMS…”
Section: Physical Factor Potential Effectmentioning
confidence: 99%